(untitled) (Studia Archaeologica, 2025)
Zooarchaeology or the study of animal remains from archaeological sites gives important information about many aspects of human societies in the past, including cultural practices, hunting strategies, diet, and also the environment. Here, we present the results of zooarchaeological analysis from Palaeolithic and Neolithic sites in eastern Mongolia. We show that horses were one of the most important species in all periods and that wild cattle (aurochs) became increasingly important in the Neolithic. It is also clear that both environment and hunting strategies changed beginning around 8500 cal BP, when precipitation increased and temperatures were warmer across East Asia. The types of species recovered from Neolithic sites show an increase in the range of animals hunted, specifically more focus on hard to catch prey like hare/rabbit (Leporids), foxes, and even birds. Species diversity decreased again in the Bronze Age with the introduction of domesticated herd animals. The results show that relationships between humans, herds, and grasslands were fundamental to the development of Mongolian society, regardless of climate change. We should envision the three pillars of pastoralism – herder-pasture-livestock – as fundamental to sustainable subsistence in Mongolia with its roots stretching back to the Palaeolithic.